Créditos da Revista ÁGORA, ISSN 0103-3557, Florianópolis v.27, n. 54, p. 1-362, jan./jun., 2017 - Ágora, Revista (ÁGORA: Arquivologia em debate, 2017)
Créditos da edição atual da Revista ÁGORA, ISSN 0103-3557, Florianópolis v.27, n. 54, p. 1-362, jan./jun., 2017.